PRT to predict pharmacokinetic profiles as part of a bioequivalence study of the drug deferasirox - A. V. Suvorova; P. A. Losenkova; Yu. V. Medvedev; E. A. Malashenko; I. E. Makarenko; A. M. Poluyanov; I. E. Shohin (Разработка и регистрация лекарственных средств)
Introduction. Deferasirox is a complexing drug and belongs to class II according to the biopharmaceutical classification system (BCS), has acidic properties and belongs to subclass “a” (acid). This class is characterized by high permeability and low solubility, which limits the absorption of the active substance into the blood. As a result, the development of drugs with an active substance that can be assigning BCS to this class is a difficult task, and for generic drugs it is also associated with a high risk of obtaining unproven equivalence during clinical trials. To minimize the above risks, a physiologically relevant test was carried out with further data processing and construction of putative pharmacokinetic profiles.Aim. The aim of the study is to conduct a physiologically relevant test (PRT) to predict in vitro pharmacokinetic profiles and compare them with in vivo data as part of a bioequivalence study of deferasirox.Materials and methods. The objects of the study are "Deferasirox, film-coated tablets, 360 mg" of a domestic manufacturer and "Jadenu®, film-coated tablets, 360 mg" (WTN22 series, expiration date until 10.2023, Novartis Pharma Stein AG, Switzerland). A physiologically relevant test was performed on the device SC PRT-6, Compliance. Quantitative analysis was carried out by HPLC-UV method.Pharmacokinetic profiles were modeled using PK-Sim® (Systems Biology Software Suite 11.2, Bayer Technology Services GmbH, Germany) based on data obtained from physiologically relevant test.Results and discussion. A physiologically relevant drug test for deferasirox was performed and release profiles were obtained, which formed the basis of a physiologically based pharmacokinetic model together with data on the physicochemical properties of the studied compound and literature data on the pharmacokinetics of deferasirox. The pharmacokinetic profiles obtained as part of the simulation on a virtual population were compared with data obtained during clinical trials.Conclusion. A physiologically relevant test for the drug deferasirox was carried out, quantitative determination in the samples was carried out by HPLC-UV. The test resulted in data that allowed prediction of pharmacokinetic profiles that reflected the same differences observed in the profiles of the test and reference drug in the comparative pharmacokinetics and bioequivalence study of deferasirox drugs.